A nationwide pest risk analysis in the context of the ongoing Japanese beetle invasion in Continental Europe: The case of metropolitan France - Poggi, Sylvain; Desneux, Nicolas; Jactel, Hervé; Tayeh, Christine; Verheggen, François (Frontiers in Insect Science, 2022)
The Japanese beetle, Popillia japonica, is native to Japan and became established in North America in the early twentieth century. The beetle was detected in Europe, first in Italy in 2014 and then in Switzerland in 2017. Metropolitan France is at the forefront of the Japanese beetle threat, due to its geographical proximity to the European populations established in the Piedmont, Lombardy and Ticino regions. An express pest risk analysis for metropolitan France was therefore conducted. The most likely pathways for entry include (i) natural dispersion, (ii) trades of plant products with adherent soil and (iii) hitchhiking behaviour, leading to a high probability of entry. The spread rate of P. japonica was also evaluated as high, resulting from natural spread as well as human activities. Given the absence of significant limiting factors, the potential impacts of P. japonica in France will likely be as important as in its current geographic distribution. Although several sources of uncertainty were highlighted throughout the evaluation, none of them has significant impact on the conclusions of the present express pest risk analysis. Measures to prevent entry, establishment and spread of P. japonica are recommended and include surveillance with pheromone traps and control via integrated pest management strategies. However, most efforts should be concentrated on eradication measures while P. japonica is still in the early stages of invasion.